203k views
1 vote
4 - 3(x-3) = 5(x+2) - 8xSolve for the variable in the equation shown

1 Answer

3 votes

Given:

The equation is,


4-3(x-3)=5(x+2)-8x

Simplify the equation,


\begin{gathered} 4-3\mleft(x-3\mright)=5\mleft(x+2\mright)-8x \\ \text{LHS}=4-3(x-3) \\ =4-3x-3*(-3) \\ =4-3x+9 \\ =13-3x\ldots\ldots\text{.}\mathrm{}(1) \\ \text{RHS}=5(x+2)-8x \\ =5x+5(2)-8x \\ =-3x+10\ldots\ldots\ldots\ldots\text{.}(2) \end{gathered}

Now,


\begin{gathered} 13-3x=-3x+10 \\ -3x=-3x+10-13 \\ -3x=-3x-3 \\ \Rightarrow-3=0 \\ \Rightarrow No\text{ solution} \end{gathered}

User Gaiazov
by
5.9k points